Factors that contribute to the financial problem: a study faced by students of UiTM Shah Alam / Shazreen Muhammad Redza - Muhammad Redza, Shazreen (2012)
College living is an exciting and challenging undertaking for most students. Moving away from mom and dad, living on their own and making decisions for themselves and having to manage own finances are just a few of roadblock they will be facing. Having a good budgeting plan in place and sticking to the plan as closely as possible can help them to survive the transition with the least stress. Moreover, the world economic conditions have been growing rapidly for the past few decades. These rapid growths have led to great changes in the level of financial awareness in every people around the world. The skill and knowledge regarding to money management and financial budgeting is very important in every individual since it will make them making decision regarding to their own personal finance. However, the financial management among college student is not in good condition since a lot of them nowadays can easily being in a debt after graduation. Facing this kind of problem at young age will affect the future of the youth who is being said as future leader. The purpose of this study is to identify the factor have the most influence towards the financial problem among college students. The college students at University Technology Mara Shah Alam (UiTM) were selected as the target respondent in the study and the major data collection method is done via questionnaire.